Legal, Social and Ethical Issues in Euthanasia - Kemi Anthony Emina (Universitas Negeri Makassar, 2021)
In the present era, there is tremendous changes have taken place in beliefs and practices pertaining to the beginning of life. Family planning and birth control instead of being condemned are now accepted as a duty and responsibility. Now abortion is legal in certain circumstances, if abortion could be legal in certain circumstances, then why is there no euthanasia law for the people who have no hope of their life? All human beings have the fundamental right to live. However, there is always a dilemma involved in letting the suffering people die and killing the innocent patient under a false pretext. It can be argued that the issues involved in euthanasia have a significant implication for the individuals in society and to the policymakers. Many people pray that they will not outlive their usefulness and became a burden to their next kin, forcing them to spend large sums of money only to postpone inevitable. Euthanasia is a controversial topic and people are becomING increasingly aware of the issues attached to it. Evidence of this is the question and argument being orchestrated in a rising volume of publication seminars conferences, court decisions and legislative proposal. This work attempt to stimulate discussion and appropriate action in dealing with this present problem. This present work concentrates on the implications involved in the human rights to live especially in the field of medicine and also aims at expositing the issues of euthanasia from legal, social and ethical perspectives.